The influence of NCE− (E = S, Se, BH3) ligands on the temperature of spin crossover in a family of iron(ii) mononuclear complexes. Issue 7 (29th May 2018) - Fei, Bin; Chen, Xiu Qin; Cai, You De; Fang, Jing-Kun; Tong, Ming Liang; Tucek, Jiri; Bao, Xin
Abstract : The temperature of spin crossover was systematically tuned by replacing the NCE − (E = S, Se, BH3 ) co-ligands in a family of mononuclear complexes. Abstract : A precise regulation of the temperature of spin crossover (SCO) is an essential task to envisage practical applications of switchable materials. Here, we present three isostructural complexes with the formula [Fe(LCl )(NCE)2 ], where LCl is the tetradentate ligand N, N ′-bis[(4-chloro-2-pyridyl)methyl]ethane-1, 2-diamine and E = S (1-S ), Se (1-Se ), and BH3 (1-BH3 ). Single-crystal X-ray diffraction, magnetic measurements, Mössbauer spectroscopy and DSC measurements have been carried out to study their SCO properties.1-S remains in a high spin state over all temperatures due to the weak ligand field strength imposed by NCS − ligands. The replacement of NCS − by NCSe − allows the occurrence of SCO around 177 K. Using NCBH3 − instead allows a further increase of the conversion temperature ( T 1/2 ) by ca. 30 K. A literature survey of complexes containing NCE − ligands was carried out to examine their influence on the SCO properties. A 50–90 K difference in T 1/2 was found between NCS − and NCSe − derivatives and a 30–50 K difference was found between NCSe − and NCBH3 − derivatives.